An Open Framework for the Reproducible Study of the Iterated Prisoner's Dilemma. Issue 1 (31st August 2016) - Knight, Vincent; Campbell, Owen; Harper, Marc; Langner, Karol M.; Campbell, James; Campbell, Thomas; Carney, Alex; Chorley, Martin; Davidson-Pilon, Cameron; Glass, Kristian; Glynatsi, Nikoleta; Ehrlich, Tomáš; et al.
The Axelrod library is an open source Python package that allows for reproducible game theoretic research into the Iterated Prisoner's Dilemma. This area of research began in the 1980s but suffers from a lack of documentation and test code. The goal of the library is to provide such a resource, with facilities for the design of new strategies and interactions between them, as well as conducting tournaments and ecological simulations for populations of strategies. With a growing collection of 139 strategies, the library is a also a platform for an original tournament that, in itself, is of interest to the game theoretic community. This paper describes the Iterated Prisoner's Dilemma, the Axelrod library and its development, and insights gained from some novel research.